Study of riverine wetlands of Bakulahi River in the interfluvial zone of Ganga and Sai Rivers, Uttar Pradesh, India - Maddheshiya S.K.; Jha M.; Tignath S.; Singh N. (My University, 2025)
Hydrogeomorphological features such as paleochannels, oxbow-lakes, meander scars, etc., are the remnants of ancient flowing rivers which scrolled and shifted to successively new courses due to various geomorphological, tectonic and climatological factors and are presently buried with younger fluvial sediments. A series of aligned hydrogeomorphological features in the interfluvial zone of the Ganga and Sai Rivers exist in the upper reaches of the currently existing Bakulahi River. Their continuity and correlation with the Bakulahi River remained unexplored as yet. The present paper aims to identify, delineate, and hydrogeomorphologically reconstruct these features in the Ganga and Sai Rivers’ interfluve and find out their association with the currently existing Bakulahi River. Remote sensing data (Landsat-8, Sentinel, and Shuttle Radar Topography Mission- Digital Elevation Models) were used to identify and delineate these paleochannels. Spatial cross-sectional profiles were generated through the Digital Elevation Model data to know the paleochannel’s longitudinal and transverse forms and dimensions. The delineated paleochannels in the satellite image were cross-verified with the electrical resistivity survey and the sedimentological analysis, which confirmed the existence of paleochannels of the Bakulahi River. The study reveals that all the hydrogeomorphological features in the interfluvial zone of the Ganga and Sai Rivers are an integral part of the currently existing Bakulahi River and concludes that the Bakulahi River was flowing from near Gouria Kalan village, Unnao district, and finally met with the Sai River at Khajurni village in Pratapgarh district. The river dynamics changed with time, possibly owing to multiple factors such as changes in energy state, sediment load, extensive deforestation, neo-tectonism, etc., which caused the loss of the continuity of the Bakulahi River. Eventually, the relics of the Bakulahi River remained as disconnected riverine wetlands at present. This study is a matter of wide concern of global interest in the diminishing riverine wetlands of flood plains. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.